Novel pyrazole–pyrazoline hybrids endowed with thioamide as antimalarial agents: their synthesis and 3D-QSAR studies. (August 2015) - Marella, Akranth; Shaquiquzzaman, Mohammad; Akhter, Mymoona; Verma, Garima; Alam, Mohammad Mumtaz
Abstract One of the most viable options to tackle the growing resistance to the antimalarial drugs is hybrid molecules. It involves combination of different scaffolds in one frame that may lead to compounds with diverse biological profiles. In this context, new hybrids of three different scaffolds viz pyrazole, pyrazoline and thiosemicarbazone moiety were incorporated into one single compound and evaluated for their in vitro schizontocidal activity against the CQ-sensitive 3D7 strain of Plasmodium falciparum. Compounds with significant in vitro antimalarial activity were further evaluated for cytotoxicity against VERO cell lines. The best active compound 48 exhibited an IC50 of 1.13 µM. The in vitro results were further validated by quantitative structure–activity relationship (QSAR).